(3JMQjQ GdebGd aj BOGH hCMcGe hahGFO jMJGL EdjgG eDOHh GdCWaGds - (3CMeO Hf eMeO Hf Ydj Hf nMnLQ GdngrjnJej GdSYOj GdCfUGQj, TgGH GdOjf TjN GdESdGe, CHh GdYHGS,J (B974 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa MedI cJGHg hHYO abO hQO Ydi ef HYV edLC eDOHh GdCWaGd CSFdI eaMeI hJObjbGJ GdCLhHg YfgG s
(3BNQgG (B:s
(3GdYGTQ CNQL GdOjdei Cf Udi Gdgd Ydjg hSde bGd CfG NGUe jhe GdbjGeI Yf GdjJje s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B234 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B152s
Keywords: (3GdSjGSI hGdGLJeGYs